Not all Online Sexual Activities Are the Same - Barrada, Juan Ramón; Ruiz-Gómez, Paula; Correa, Ana Belén; Castro, Ángel (Frontiers in Psychology, 2019)
Young people’s use and participation in online sexual activities (OSA) has increased in the past two decades and has changed their behavior in the area of sexuality. The existing literature has some important limitations, concerning the assessment of the construct and its orientation toward problematic use, while ignoring its healthy use or social participation and its relationship with well-being. The main objective of this study was to analyze the relationships between the three types of OSA (compulsive, isolated, and social) proposed by Delmonico and Miller, as well as offline sexual behavior, and psychosexual well-being. It was also necessary to evaluate the factor structure of the Internet Sexual Screening Test (ISST). Participants were 1,147 university students of both sexes, aged between 18 and 26 years, who completed a battery of online questionnaires. The main finding of the study is that, when controlling for other online sexual behavior, different types of OSA evaluated relate differently to offline sexual behavior and to psychosexual well-being, and that most young people made healthy use and participation of OSA. It also presents a new structure of the ISST. The discussion emphasizes the need to recognize the positive consequences of OSA to implement programs for the promotion of sexual health.